Integration of small hydro turbines into existing water conduit of an irrigation dependent power plant – A case study. (2021) - Kurulekar, M.; Kumar, K.; Joshi, Shardul; Kurulekar, M.; Kulkarni, Abhijeet
Abstract: Hydro energy is one of the richest and most useful renewable energy sources in the world. In an irrigation-based storage reservoir, agricultural to hydro power water transfer is important. A tradeoff between irrigation and power generation is essential in order to achieve optimal social benefits. Most of the irrigation based hydro turbines employ the reaction type turbines due to the advantages of low/medium head and high discharge through the irrigation canals. The release of water through irrigation gates is affected during the lower release of water for irrigation, flora and fauna and drinking. The power units are of reaction type hydro turbines could not able to tap the energy during the lower release due to the restriction on operational limitations, the turbine may subject to cavitation and leads to noise and vibration causes subsequent fatal failure of parts and catastrophic accident on the plant. This condition leads to reasonable generation loss to the power generating units. A pilot study on Dhom (2x1 MW) irrigation dependent hydroelectric plant, Mahagenco, Satara, Maharastra has been conducted in order to tap the water during the lower release and flood scenario from the reservoirs. The modification has been suggested in the existing layout of penstock section at main inlet valve. This paper emphasizes on utilizing untapped energy by integrating small hydro turbine into the existing water conduit in an irrigation dependent hydro power plant. Incorporation of inline hydro power units with existing water conductor system would yield additional power generation of 2.592 Million units of energy per year. Further, the plant capacity factor could be increased from 0.315 to 0.463. The additional power generation can be used for internal loads of the power house.